Antiendotoksinovyj immunitet v reakcii srocnoj adaptacii k fiziceskim nagruzkam - Oparina, O. N. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The purpose of this paper was to study the indices of endotoxin content in blood plasma and the indices of humoral and leucocytar immunity to endotoxin in 38 athletes and 13 nonathletes before and after physical loads. It was shown that systemic endotoxinemia and antiendotoxin immunity deficiency can develop after physical loads. These data suggest that the antiendotoxin immunity can play some role in adaptation to physical loads.